DC-DC converter based power management for go green applications - W, Abitha Memala; Bhuvaneswari, C.; Shyni, S.M.; Sheeba, G. Merlin; Mahendra, Modi Surya; Jaishree, V (Institute of Advanced Engineering and Science, 2019)
A non-isolated tri-port converter is a fully compact and functional system by the integration of basic converters. This can be used for renewable energy applications. This converter is capable of achieving different switching patterns of power flow between the source and load, interfaced sources of various voltage and current levels with the dc grid. This tri-port converter has to be used for continuous power distribution of rechargeable battery, photovoltaic panels and load. Due to the implementation of this dc-dc converter some operations like buck, boost and buck-boost operations became easy. Use of this converter helps in easy implementation of the system. The solar PV panel implementation boosts the system to a high level and bidirectional flow became easy from source to load and vice versa